The Notion of Soul as Horizon in the Liber de Causis - Prendas Garro, Róger (2026)
This article seeks to explore how the Liber de Causis understands the concept of the souland its importance in medieval scholasticism, employing the category of horizon insofaras it allows the emanationist narrative proper to Neoplatonism to be articulated with thescholastic worldview, along with the implications that follow from its metaphysics for itspolitical praxis.